Polycyclic aromatic hydrocarbons (PAHs) skin permeation rates change with simultaneous exposures to solar ultraviolet radiation (UV-S). (1st May 2018) - Hopf, Nancy B.; Spring, Philipp; Hirt-Burri, Nathalie; Jimenez, Silvia; Sutter, Benjamin; Vernez, David; Berthet, Aurelie
Highlights: PAH skin permeation with and without co-exposures to UV-S had low permeation rates. Skin permeation rates decreased 50% for naphthalene and BaP when co-exposed to UV-S. Anthracene, pyrene and chrysene permeation rates increased when co-exposed to UV-S. p53 expression increased with increasing UV-S exposures but not with PAH exposure. Abstract: Road construction workers are simultaneously exposed to two carcinogens; solar ultraviolet (UV-S) radiation and polycyclic aromatic hydrocarbons (PAHs) in bitumen emissions. The combined exposure may lead to photogenotoxicity and enhanced PAH skin permeation rates. Skin permeation rates (J) for selected PAHs in a mixture (PAH-mix) or in bitumen fume condensate (BFC) with and without UV-S co-exposures were measured with in vitro flow-through diffusion cells mounted with human viable skin and results compared. Possible biomarkers were explored. J s were greater with UV-S for naphthalene, anthracene, and pyrene in BFC (0.08–0.1 ng/cm 2 /h) compared to without (0.02–0.26 ng/cm 2 /h). This was true for anthracene, pyrene, and chrysene in the PAH-mix. Naphthalene and benzo(a)pyrene (BaP) in the PAH-mix had greater Js without (0.97–13.01 ng/cm 2 /h) compared to with UV-S (0.40–6.35 ng/cm 2 /h). Time until permeation (Tlags ) in the PAH-mix were generally shorter compared to the BFC, and they ranged from 1 to 13 h. The vehicle matrix could potentially be the reason for this discrepancy as BFC contains additional not identified substances. Qualitative interpretation of p53 suggested a dose-response with UV-S, and somewhat with the co-exposures. MMP1, p65 and cKIT were not exploitable. Although not statistically different, PAHs permeate human viable skin faster with simultaneous exposures to UV.